Nurses’ Attitudes Towards Involving Relatives in Nursing Care: - Cross-sectional Study - Aasan, Olaug Julie; Bjerkan, Jorunn; Torvik, Karin; Nordtug, Bente (Nordisk Tidsskrift for Helseforskning, 2025)
In the future there will be more patients in need of care and fewer nurses. Relatives will have a more extensive caring role, which makes nurses’ collaboration with relatives important. The aim of the study was to investigate nurses’ attitudes towards involving relatives and see if there were differences between nurses in the municipal health service and hospitals. In addition, whether there were conditions that influenced their attitudes. The study was cross-sectional using a questionnaire (Importance in Nursing Care – Nurses’ Attitudes (FINC – NA) with a convenience sample of nurses from villages, densely populated areas, and small towns in central Norway (N = 318). No differences were found between nurses in the municipal health service and hospitals, and it was usual to show care for relatives. Relatives were seen as a resource for patients, and as an important collaboration partner. Nurses with further education had more positive attitudes.
Keywords: Nurses; Attitudes; Relatives; Cross-sectional study; Municipal health services; Hospital care